DIGITAL CSR MERDEKA ADVERTISEMENTS AND NATIONAL UNITY NARRATIVES: A MULTIMODAL AND NLP ANALYSIS OF MALAYSIAN SOCIAL MEDIA (2019–2023) - JAMILAH AHMAD , SURIATI SAAD , NURSHIMA SARUDIN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study investigates how Malaysian corporations construct national unity narratives through CSR Merdeka advertisements. Analysing a corpus of campaigns from Petronas, Tenaga Nasional, and Telekom Malaysia across social media platforms, the research employs a mixed-methods framework integrating natural language processing, multimodal content analysis, and Social Identity Theory. The analysis uncovered six dominant unity narratives: multicultural harmony, shared resilience, intergenerational continuity, cultural celebration, nation-building, and everyday kindness. Advertisements leveraging authentic ethnic representation and emotional storytelling achieved significantly higher engagement, with YouTube and Facebook serving as the most effective platforms. Sentiment and emotional analysis of audience comments revealed overwhelmingly positive responses, primarily characterized by gratitude, nostalgia, and pride. Statistical analysis confirmed that emotionally intense narratives and the strategic use of behavioural nudges drove significantly higher audience interaction. However, the study identifies a critical gap between high digital engagement and substantive unity-building, marked by a notable underrepresentation of East Malaysian communities and limited evidence of long-term behavioural impact. It concludes that while these advertisements are powerful in shaping national sentiment, their potential for fostering genuine social cohesion remains unrealized without more inclusive representation and initiatives that bridge online engagement with real-world action.